Microstructures and Texture of Inconel 718 Alloy Fabricated by Selective Laser Melting - Shuai, Li (2016)
Inconel 718 nick base superalloy samples were fabricated by selective laser melting from the powder. The microstructure examinations reveal that fine cellular and dendritic structures with a size smaller than 1µm were formed in the laser track due to the rapid cooling speed. In order to investigate the influence of the anisotropy, two scanning strategies were used namely bidirectional and rotate 90° between neighboring layers in this study. The Inverse Polar Figure (IPF) acquired by electron backscatter diffraction (EBSD) proves that both of them show strong texture long the building directional. However, the texture can be significantly reduced by adjusting the scanning strategies.